Asian Summer Monsoon and Orographic Winds Change the Pollen Flow in the Hengduan Mountains, Southwestern China - Hui Zeng; Zi‐Yu Wang; Gui‐Xing Chen; David K. Ferguson; Yu‐Fei Wang; Yi‐Feng Yao (Geophysical Research Letters)
Abstract Unlike plains, mountains provide diverse habitats for various biomes due to complex topography and large altitudinal differences. It is crucial for objectively reconstructing deep‐time biodiversity changes that the pollen source, dispersal, and driving forces in montane ecosystems are studied. Here, we investigate surface soil samples from different vertical zones in the Hengduan Mountains. Results show the pollen assemblages generally reflect the dominant components of the warm temperate coniferous forest and the cold temperate coniferous and sclerophyllous oak mixed forest, but exotic anemophilous pollen like Pinus (53.4%), Alnus (3.5%), Tsuga (1.1%), and Juglans (0.5%) are found in the subalpine scrub and meadows by upslope flow. The atmospheric reanalysis data suggests that the Asian summer monsoon and diurnally‐varying orographic winds may jointly drive the upslope and downslope pollen flows. These new findings provide basic scientific data and potential interpretations for the reconstructions of past vegetation and plant diversity in global montane ecosystems.